"The devil's in the detail": Release of an expanded, enhanced and dynamically revised forensic STR Sequence Guide. (May 2018) - Phillips, C.; Gettings, K. Butler; King, J.L.; Ballard, D.; Bodner, M.; Borsuk, L.; Parson, W.
Highlights: The sequence template file published with 2016 ISFG STR sequence nomenclature guidelines is comprehensively revised. Listed forensic STRs have been expanded to include loci less commonly used but in need of detailed sequence descriptions. A wide range of sequence variation features in and around forensic STRs have been identified and their annotations added to the new guide. The sequence guide is now available as an FTP download allowing dynamic revisions and includes a date-stamped change log to detail future changes. Abstract: The STR sequence template file published in 2016 as part of the considerations from the DNA Commission of the International Society for Forensic Genetics on minimal STR sequence nomenclature requirements, has been comprehensively revised and audited using the latest GRCh38 genome assembly. The list of forensic STRs characterized was expanded by including supplementary autosomal, X- and Y-chromosome microsatellites in less common use for routine DNA profiling, but some likely to be adopted in future massively parallel sequencing (MPS) STR panels. We outline several aspects of sequence alignment and annotation that required care and attention to detail when comparing sequences to GRCh37 and GRCh38 assemblies, as well as the necessary matching of MPS-based allele descriptions to previously established repeat region structures described in initial sequencing studies of the less well known forensic STRs. The revised sequence guide is now available in a dynamically updated FTP format from the STRidER website with a date-stamped change log to allow users to explore their own MPS data with the most up-to-date forensic STR sequence information compiled in a simple guide.